(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2024)
Purpose: This study discusses the concept of compulsory citizenship behavior (CCB) and identifies the relationships between CCB, organizational identification, and employee silence bearing in mind the Conservation of Resources Theory (COR). In other words, the study examines CCB’s effect on employee silence as well as whether organizational identification has a mediating role in this effect. Methodology: Data were obtained by means of surveys from the employees of the manufacturing sector in a province in Turkey. Data were analyzed using the IBM SPSS, PROCESS Macro, and Amos package software in line with the purpose of the study. Results: The findings show that CCB negatively affects organizational identification and positively affects employee silence. Furthermore, organizational identification was found to negatively affect employee silence. The findings regarding mediation indicate that organizational identification has a mediating role in CCB’s effect on employee silence. Conclusion: As a result, it was determined that CCB would have negative consequences. The perception of CCB increased employee silence behavior both directly and indirectly (by reducing identification).